2005
DOI: 10.1001/archotol.131.7.605
|View full text |Cite
|
Sign up to set email alerts
|

Age as a Prognostic Factor for Complications of Major Head and Neck Surgery

Abstract: To determine if age alone is a prognostic indicator of surgical outcomes for major head and neck procedures.Design: Retrospective cohort study over a 4-year period.Setting: Academic referral center, institutional practice, hospitalized care.Patients: Included in this study were patients who had undergone ablative, reconstructive, and other major surgical procedures of the head and neck, including neck dissection, laryngectomy, maxillectomy, thyroidectomy with lymphadenectomy, and composite resection of the ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 20 publications
(26 reference statements)
9
88
2
2
Order By: Relevance
“…Three studies calculated CCI scores (3,21,22) and only one study used the KFI (11). Therefore, the comorbidity-complication analysis of the review was based on the ASA scoring system.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies calculated CCI scores (3,21,22) and only one study used the KFI (11). Therefore, the comorbidity-complication analysis of the review was based on the ASA scoring system.…”
Section: Methodsmentioning
confidence: 99%
“…Age and sex were not prognostic factors in our study. Studies on head and neck tumors have shown no difference in outcome in older patients when compared with the younger patients [12,13]. Though TNM classification has been universally accepted as a tool to predict survival rates we did not find it useful in our study.…”
Section: Discussionmentioning
confidence: 57%
“…Most importantly, the functional outcomes were similar between old and young patients (Nao et al, 2011). In an article investigating the impact of age on patients submitted to major head and neck procedures, age wasn't considered as a major prognostic factor for surgical outcome (Boruk et al, 2005). In our own experience, age is no longer considered as significant when considering the reconstruction modality to be employed, being replaced by performance-status evaluation.…”
Section: Wwwintechopencommentioning
confidence: 94%